Physical mechanism of progressive breakdown in gate oxides - Palumbo, Félix Roberto Mario (2014)
The definition of the basic physical mechanisms of the dielectric breakdown (BD) phenomenon is still an open area of research. In particular, in advanced complementary metal-oxide-semiconductor (CMOS) circuits, the BD of gate dielectrics occurs in the regime of relatively low voltage and very high electric field; this is of enormous technological importance, and thus widely investigated but still not well understood. Such BD is characterized by a gradual, progressive growth of the gate leakage through a localized BD spot. In this paper, we report for the first time experimental data and a model which provide understanding of the main physical mechanism responsible for the progressive BD growth. We demonstrate the ability to control the breakdown growth rate of a number of gate dielectrics and provide a physical model of the observed behavior, allowing to considerably improve the reliability margins of CMOS circuits by choosing a correct combination of voltage, thickness, and thermal conductivity of the gate dielectric.